2019
DOI: 10.1016/j.clae.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and repeatability of four different devices to measure non-invasive tear breakup time (NIBUT)

Abstract: Purpose: Since tear film stability can be affected by fluorescein, the International Dry Eye Workshop (DEWSII) recommended non-invasive measurement of tear breakup time (NIBUT). The aim of this study was to investigate the agreement and repeatability of four different instruments in the measurement of NIBUT.Methods: 72 participants (mean 24.2 ± 3.6 years) were recruited for this multi-centre, cross-sectional study. NIBUT was measured three times from one eye using each of the instruments in randomized order on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…It can serve as an interferometer for the observation of the tear film lipid layer and allows for the measurement of noninvasive tear breakup time after inserting a grid. 30 It is similar to the Tearscope (Keeler Ltd., Windsor, United Kingdom), but it contains an integrated stopwatch and a light-emitting diode that can be used as a light source. It can be used as a handheld device, or it can be connected to a slit lamp.…”
mentioning
confidence: 99%
“…It can serve as an interferometer for the observation of the tear film lipid layer and allows for the measurement of noninvasive tear breakup time after inserting a grid. 30 It is similar to the Tearscope (Keeler Ltd., Windsor, United Kingdom), but it contains an integrated stopwatch and a light-emitting diode that can be used as a light source. It can be used as a handheld device, or it can be connected to a slit lamp.…”
mentioning
confidence: 99%
“…16,26,27 As per the Tear Film and Ocular Surface Society Dry Eye Workshop II (TFOS DEWS II), the cutoff value for noninvasive tear breakup time is ≥10 seconds for normal eyes; using traditional methods, similar cutoff values were also reported by other studies. 22,28,29 In the present study, noninvasive tear breakup time is a marker of the stability of the pre-corneal tear film with a cutoff value of <10 seconds. In the 4-week study, improvement in tear breakup time was greater than the clinically meaningful level of 2.5 seconds.…”
Section: Discussionmentioning
confidence: 85%
“…The ring pattern can be illuminated by white or infrared light. This instrument measurement results in two outcomes, the first disruption in the projected placido rings (noninvasive tear breakup time first) and an average tear film breakup of the sections across the cornea (noninvasive tear breakup time average) 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandlitz et al [17] recently reported that objective measurement of the NIBUT using the Keratograph 5 M (Oculus Optikgeräte GmbH, Wetzlar, Germany) showed good repeatability and reasonable agreement with subjective NIBUT measurement using the Tearscope Plus (Keeler, Windsor, UK), Polaris (bon Optic, Lübeck, Germany), and EasyTear Viewplus (Easytear, Rovereto, Italy), which also support viability of the NIBUT in the diagnosis and treatment of DED [15].…”
Section: Noninvasive Tear Break-up Time (Nitbut)mentioning
confidence: 80%